Hepatoprotective effect of methanolic Tanacetum parthenium extract on CCl4-induced liver damage in rats - Mahmoodzadeh, Yavar (Toxicol Rep, 2017)
The purpose of this study was to investigate the effects of Tanacetum Parthenium Extract (TPE) on Lipid peroxidation, antioxidant enzymes, biochemical factors, and liver enzymes in the rats damaged by Carbon Tetrachloride (CCl4). 54 male Wistar rats were divided into 9 groups each consisting of 6 rats. Two of the groups were control groups (normal and damage control groups), 4 of them were exposure groups which were respectively administered with 40, 80, and 120 mg/kg of TPE and silymarin for 14 days before being damaged by CCl4, and the other 3 groups were post-treatment groups which received 80 and 120 mg/kg of TPE and silymarin 2, 6, 24, and 48 h after being injected with CCl4. At the end of the study, biochemical factors, serum liver enzymes, malondialdehyde level, antioxidant enzymes, and liver morphology were assayed. Pre- and post-treatment with TPE could significantly decrease ALT, AST, ALP, TG, LDL, TC, and glucose levels and increase HDL, and albumin levels and catalase, SOD, and GPx activities compared to the CCl4-damaged control group. The results of this study are indicative of the antioxidant activity of TPE, its potential hepatoprotective effects, and its probable therapeutic properties for laboratory animals damaged by CCl4.